The challenge of international business - Buckley, Peter J. (Palgrave Macmillan, 2004)
Research in international business has been at its most successful when it has been a collective enterprise focused on a key empirical issue in the evolving global economy, says Buckley (international business, U. of Leeds), and it lacks such an issue now. With the help of colleagues from around Europe, he assesses the becalmed state of the discipline, the response to it, knowledge management in multinational firms, and empirics.